Trends in per capita ecological footprint and biocapacity in China 1949–2013. Issue 2 (3rd April 2017) - Cao, Yuan; Chen, Chengzhong; Ge, Xuguang
ABSTRACT: This paper proposes two concepts: the ecological footprint component index (EFCI) and the biocapacity component index (BCCI), based on the ecological footprint (EF) and Shannon entropy approaches. Per capita EFCI and BCCI in China 1949–2013 are analyzed using empirical mode decomposition (EMD). Nonlinear models of per capita EFCI and BCCI in China 1949–2013 are presented and their cycles and predictions from 2014 to 2023 are analyzed. The results over the last 65 years show: (1) EFCI in China has increased constantly with fluctuations, while BCCI has slowly decreased. Their annual change rates are 2.81% and −1.26%, respectively. The increasing EFCI indicates a gradual improvement in China's sustainable development potential; the decreasing BCCI indicates severe environmental and population challenges. (2) The cycles of per capita EFCI have periods of 5.4 and 16.3 years, while cycles of per capita BCCI have periods of 3.6, 13, and 21.7 years. The predictive models indicate that EFCI will first decrease, reaching 0.02725 in 2014, and will subsequently increase to 0.03261 in 2021. BCCI will increase, reaching 0.01365 in 2014 and 0.01541 in 2022. EFCI and BCCI will reach 0.03037 and 0.01537, respectively, in 2023. Policymakers should ensure that the EFCI and BCCI increase in 2023.